UMA ARQUITETURA BASEADA EM WEB SERVICES SEMÂNTICOS PARA AGRUPAMENTO DOS AGENTES NEGOCIANTES NO AMBIENTE ICS DE COMÉRCIO ELETRÔNICO - Tomaz, Ricardo Ferraz (2003)
This work is part of the ICS project which is being developed at Federal University of Maranhão under the Coordination of Prof. Phd. Sofiane Labidi. This project is aiming to develop an effective Intelligent B2B e-commerce System. The ICS is based on the mobile and intelligent software agent s technology and has three main characteristics: the electronic commerce lifecycle, the user modeling and the proposed ontologies on each phase of the lifecycle. One of the main phases of the ICS lifecycle is the matchmaking. The matchmaking is the process in which agents, representing traders that are interested in having exchange of economic value, are put in contact with potential counterparts to negotiate. In this work, we develope the proposed architecture of the ICS and highlight one of its main phases: the matching process, attributed to the Matchmaker Agent. We propose the use of the Web Services as assembly blocks for the Matchmaker agent, allied to the Semantic Web perspective, as an alternative to make possible the semantic crossing between the buyers' requests and the suppliers' advertisements, allowing the automatic discovery of the offered services that really interest the clients.